Hybridization of carboxymethyl chitosan with bimetallic MOFs to construct renewable metal ion "warehouses" with rapid sterilization and long-term antibacterial effects. (1st February 2023) - Li, Hao; Zhang, Yuwei; Zhang, Yuancheng; Wei, Fuxiang; Deng, Yongfu; Lin, Zhenhao; Xu, Chuanhui; Fu, Lihua; Lin, Baofeng
Abstract: Pathogens transmitted through the water environment pose a great threat to human health. Hence developing more reliable and efficient antibacterial materials to eliminate bacterium in water environments is urgent. Herein, we posed a novel strategy of interweaving carboxymethyl chitosan (CMCS) and Ag/Cu-MOFs to construct renewable Ag/Cu-BTC@CMCS composite beads with rapid sterilization, long-term antibacterial effects and high biosafety. Characterizations revealed that CMCS and bimetallic MOFs act as the "warehouses" of metal ions and played key roles in anchoring, storage, delivery, and controlled release of metal ions. The synergistic antibacterial effect achieved by the combination of Ag + and Cu 2+ provides the composite beads with high antibacterial efficiency, resulting in low minimum inhibitory concentrations (0.32 mg/mL against E . coli and 0.16 mg/mL against S . aureus ) and over 99.9 % bacteria killing rate. Benefiting from the rapid release of metal ions from polymer chains and the long-term release from MOFs, the composite beads can effectively sterilize the simulated swimming pool water in 2 h and persistently inhibit bacterial reproduction over 48 h, and show a safe level of residual heavy metals because of the chelation of CMCS. This work provides new insights and promises a strategy for the design and commercial application of novel water fungicides. Graphical abstract: Unlabelled Image